Dentistry, Dental Practice, and the Community - Brian A. Burt, Stephen A. Eklund, with a chapter contributed (Blackwell Synergy, 2000)
The authors do not state the audience for which this text is intended, but as one reads, its suitability for several audiences emerges. For dental students, this text is quite comprehensive in explaining all that is, or can be, accomplished by public health dentists, and all that has been contributed to society by public health dentistry.